2020
DOI: 10.21033/wp-2020-15
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the Marginal Propensity to Consume: Evidence from Covid-19 Stimulus Pay

Abstract: We identify 16,016 recipients of Covid-19 Economic Impact Payments in anonymized transaction-level debit card data from Facteus. We use an event study framework to show that in the two weeks following a sudden $1,200 payment from the IRS, consumers immediately increased spending by an average of $577, implying a marginal propensity to consume (MPC) of 48%. Consumer spending falls back to normal levels after two weeks. Stimulus recipients who live paycheck-to-paycheck spend 68% of the stimulus payment immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…While the circumstances of these two household types are different, they have similar challenges due to liquidity. There is an inverse relationship between household liquidity and the MPC resulting from a stimulus payment as households with low liquidity tend to have higher MPCs (Armantier et al, 2021;Baker et al, 2020;Coibion et al, 2020;Karger & Rajan, 2021). Studies from the United States on the 2001 and 2008 stimulus exhibited similar relationships between liquidity and MPC (Parker, Souleles, Johnson, & McClelland, 2013).…”
Section: International Journal Of Economics and Financementioning
confidence: 99%
See 2 more Smart Citations
“…While the circumstances of these two household types are different, they have similar challenges due to liquidity. There is an inverse relationship between household liquidity and the MPC resulting from a stimulus payment as households with low liquidity tend to have higher MPCs (Armantier et al, 2021;Baker et al, 2020;Coibion et al, 2020;Karger & Rajan, 2021). Studies from the United States on the 2001 and 2008 stimulus exhibited similar relationships between liquidity and MPC (Parker, Souleles, Johnson, & McClelland, 2013).…”
Section: International Journal Of Economics and Financementioning
confidence: 99%
“…There exists a significant base of information and research on the MPC that arises from stimulus payments. Recently, studies from 2020 and 2021 about the MPC resulting from stimulus payments in the United States (Economic Impact Payments) provide many examples of how MPC can be measured, the challenges of measuring it, and the heterogeneity amongst subsidy recipients' reactions to receiving payments (Armantier, Goldman, Kosar, & van der Klaauw, 2021;Baker, Foarrokhnia, Meyer, Pagel, & Yannelis, 2020;Coibion, Gorodnichenko, & Weber, 2020;Karger & Rajan, 2021). These studies all demonstrated that government stimulus has varying effects on spending that depend on an individual's or household's economic situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the effect of the stimulus payment passed under the CARES Act on consumer spending and saving behavior. The marginal propensity to spend out of the stimulus payment is found to be inversely related to household income (Chetty et al, 2020;Karger & Rajan, 2021;Sahm et al, 2020) and expectations of future negative income shocks such as job loss and UI benefit reduction (Baker et al, 2020), but positively related to local cost of living (Misra et al, 2021).…”
Section: Related Literature and Contributionsmentioning
confidence: 99%
“…• No smoothing: This path uses estimates of the impact on GDP from the various provisions of ARP from Edelberg and Sheiner (2021), along with assumptions about when the provisions will be spent. This path takes on board Karger and Rajan's (2020) finding that the CARES Act checks sent to households were spent quickly.…”
Section: The Models' Estimates Of the Inflationary Effects Of Arp Due To Resource Pressuresmentioning
confidence: 99%